Life's work : inspirational stories for the workplace and the heart - Kong, Francis J. (Makati City : Business Matters Publishing, 1999)
"Are you overwhelmed with work and with life? Does it feel like deadlines and quotas and meetings and profit-making have taken over your life? Indeed, work demands a great deal from us. In the process of making time for the urgent, we often lose sight of the important. This book presents stories that will help you move in the workplace and in life with greater purpose and meaning."--Cover.
Keywords: Experience -- Religious aspects; Work -- Moral and ethical aspects; Christian life